Teaching and testing of English listening and speaking in secondary schools in Nepal: Pretend for praxis? - Rana, Kesh; Rana, Karna (Journal of NELTA, 2019)
Secondary English course requires testing of four skills: listening, speaking, reading and writing independently. Secondary Education Examination (SEE) board conducts a written examination, which includes reading and writing skills, through different centres and English teachers are responsible to test students’ listening and speaking tests in their own schools and submit grades to District Education Office. Semi-structured interviews with secondary English teachers in private schools and school graduates investigated how the teachers practice listening and speaking skills in the classrooms and administer aural-oral tests. Findings indicate that private schools in the capital city have mandated English-only for communication in school premises with an expectation to develop students’ English language proficiency. Teachers focused on centre-based written examination and less emphasised the teaching and testing of listening and speaking skills. Teachers’ random assessment of students’ aural-oral skills without formal tests supported in declining the teaching of these skills. This article suggests that for realizing the examination effective, sustainable system needs to be developed for teachers to teach all language skills equitably.